Proyecto de factibilidad para la creación de un complejo deportivo de canchas múltiples en el cantón Zamora de la provincia de Zamora Chinchipe para el año 2015 - Aldaz Guazhima, Mayra Andrea (2016)
In the canton Zamora, there is a sports complex with tennis multiple use that provide safety and above all having different options for practicing sports such as basketball, soccer and Equavolley likewise, it has been evident that in this Canton there an increase in diseases caused by sedentary lifestyle and stress; for this reason arises the idea of this proposal, the same as with its implementation will give a personalized service to citizens, to practice their favorite sport even at night and have no problem with the weather. Therefore, the following problem described Research: Is the creation and implementation of a Multi Sports Complex Courts in the canton Zamora, Province of Zamora Chinchipe be feasible? The overall objective of this study is to "determine the commercial viability of the proposed implementation of a sports complex multiple courts in the canton Zamora." With the help of different scientific research methods such as inductive, deductive, statistical, descriptive, and research techniques such as direct observation and survey were able to obtain reliable information on the needs, tastes and preferences of users of a sports complex. The results of the study show the tabulation and analysis of 375 surveys of the economically active population (applicants) and 7 companies (providers) that offer the service of tennis in the Zamora Canton. In the discussion the four studies are to be applied in a project feasibility. Which starts by the market study, which indicates that the effective demand is 180,989 visits in the first year of life of the project and also an offer of 49,504 visits, and unmet demand for 131,485 visits, which allowed us to determine that the project can or should run. Then there is the technical study, which states that the size of the company according to its installed capacity and used is 64,512 visits in the first year. In terms of location the sports complex multiple courts will be located in the Zamora Canton, in the district on November 10 at Av. Alonso de Mercadillo, Av. Del Maestro and Spanish Steps Daniel Martinez, for having all the basic services, availability of labor, ease of parking, transportation and good environment. In the engineering project is the flow chart of service all phases regarding the daily care is 224 persons, a description of staffing requirements, computer equipment and sports equipment also the distribution of the plant is also done, as well. Also an administrative study which states that the sports complex will be established as a limited liability company was held, with its name Multi Sports Complex Tennis Zamora Cia. Ltda. The duration is ten years from the date of registration in the Superintendency of Companies. The investment required for the implementation of the project is USD $724,389.15 dollars of the United States of America, funding will be internal and external costs for the first year are $ 155,042.19 dollars of the United States of America and revenues of USD $ 249,240.38 dollars of the United States of America, the break-even point, occurs when the sports complex has an installed capacity of 41.81% and an income of USD $ 104,216.06 States dollars States, net income is $ 56,208.06 dollars of the United States in the first year. The results of the financial evaluation indicates that the project is not enforceable by the following financial ratios: NPV is - USD $ 461,118.94 dollars from the United States, less than one; Internal Rate of Return is -26.23% lower than the rate of cost of capital; Benefit Cost Ratio is USD $1.69 USD United States of America, which means that it will have USD $0.69 cents of the United States of America as income per dollar invested; not recover investment over the life of the project; in the sensitivity analysis, the project supports a 5% increase in costs and declining revenues. Then there is an analysis of the environmental and social impact it can have the project in Zamora Canton. Finally, conclusions, recommendations, bibliography, annexes themselves that complement the research work presented.